Occupational Health and Safety Risk Assessment of Surabaya Pump Houses using the HIRARC (Hazard Identification, Risk Assessment, and Risk Control) Method - Reza Aulia Akbar; Maria Anityasari; Renaldi Jafras Arriyanto; Ignatius Dixon Melchior; Andi Candra Septaprasetya; Tri Broto Santoso (LPPM, Institut Teknologi Sepuluh Nopember, Indonesia, 2025)
Heavy rainfall caused by climate change has led many Indonesian cities to build pump houses to remove excess water and prevent flooding. While pump performance is critical for protecting urban communities, the health and safety of pump house workers has received little attention. Because their work is seasonal, occupational health and safety (OHS) in pump houses is often overlooked,even though protecting workers is essential for ensuring reliable pump operations during emergencies. This study applies the HIRARC (Hazard Identification, Risk Assessment, and Risk Control) method, commonly used in manufacturing, to assess risks in pump house operations. Field data were collected from four representative pump houses in Surabaya, with findings intended for broader application to 61 pump houses in the city. The results highlight urgent actions needed to improve worker safety and propose practical measures to strengthen OHS practices. These findings provide valuable insights for other Indonesian cities seeking to enhance their safety culture and ensure the resilience of flood control infrastructure.